STRATEGI CERDAS DAN AMAN MENGGUNAKAN MEDIA SOSIAL BAGI GENERASI X DAN Z - Aribia Razzina Ainun Nisa; Rafif, Muhammad; Maria Yuniati Baolifa Betore Kerans; Yulanda Athina Zahra; Pangestu Adi Prasetio; Siti Chonisatul Fatimah; Arif Murti Rozamuri (Politeknik Negeri Sriwijaya, 2024)
Technological advancements have brought significant positive impacts to daily life, but they have also posed new challenges, particularly concerning the rising cases of online fraud targeting Generations X and Z. This article highlights the main issue at hand: the lack of knowledge and awareness among these groups, making them susceptible to financial and psychological losses due to online fraud and scams. In response to this issue, the workshop